The Latin American Thoracic Association (ALAT): 30 Years of History (2020)
The Latin American Thoracic Association (ALAT) first began to take shape in Barcelona, where an international scientific program launched in the early 1980s had received significant scientific contributions from many Latin American researchers, but which had limited influence in the Ibero-American scene. That was the situation in October 1990, when Manuel Cosío, an internationally renowned Spanish pulmonologist (McGill University) and Roberto Rodríguez Roisin (Hospital Clínic) organized the “I Ibero-American Course in Pulmonology”, with 250 attendees and 51 Latin American and Spanish speakers who presented all their work in Spanish. The participation of Bartolomé Celli, E. Fernández, Manuel Giménez, Alejandro Grassino, Manel Jordana, Carmen Lisboa, Eulo LupiHerrera, Manuel Oyarzún, Daniel Rodenstein, Moisés Selman, Iasha Sznajder, and NOE Zamel generated considerable interest. The event was a great success and not only was the objective achieved (“. . .to gather a group of international experts in the field of respiratory medicine with the common denominator of a common language. . .”), but a commitment was made to continue with these meetings, although they would henceforth be held in the IberoAmerican region under the name “Ibero-American Pulmonology Congress” to reflect the impact that had been made. Subsequent congresses took place in: II. Acapulco (1992); III. Vina˜ del Mar (1994); and, IV. Caracas (1996), chaired by Moisés Selman, Rodrigo Moreno and Carlos Tálamo, respectively. (Tomado de la introducción)